Causal links between foreign capital inflows and economic growth: empirical evidence from Nigeria - Jibir, A.; Francis, S.J. (Wayamba University of Sri Lanka, 2016)
The impact of foreign capital inflows on domestic investment in developing countries cannot be over emphasized. This study is designed to empirically examine the causal link between foreign capital inflows and economic growth in Nigeria. Time series data were employed spanning from 1970 to 2014. The study employed Granger causality test, co-integration and error correction mechanism as the major tools of analysis. Granger causality test showed a unidirectional causality among the components of capital inflows used in the study except remittances and real GDP. The result also indicated that there is long run relationship between capital inflows and economic growth. The policy implication that can be drawn from the above finding is that all the foreign capital components used in the study are very important sources of capital for Nigeria to finance its underdeveloped infrastructural base and pave way for growth and development of the country. What is more important is, foreign capital inflows will further help in setting a turning point for the progressive structural transformation of the country’s economy by and largely in oil based economy to a growing and diversified economy with expanding industrial, service and agricultural sector though creating job opportunities, reducing poverty and overall economic performance of Nigerian economy. The paper recommends that government should ensure proper channeling of foreign capital into productive sectors of the economy, create enabling environment and macroeconomic stability and encourage domestic savings and investment in the country.
Keywords: Economic growth; foreign capital; Granger causality